-t=-9

Simple and best practice solution for -t=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -t=-9 equation:


Simplifying
-1t = -9

Solving
-1t = -9

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '-1'.
t = 9

Simplifying
t = 9

See similar equations:

| K+(-11)=-4 | | 6-5x=3x+22 | | n+10=59 | | 2x^2+14x+49=8 | | 2y+28=54 | | ln(5x-5)=5 | | x^2+13.89x=2400 | | x^2+50x=2400 | | 12y=44 | | 15z-2=4(3z+26) | | 13z-1z= | | 4x^2-43x+7=0 | | 4y-10= | | -5.3=2.2x-8.6 | | 36+6x=-12x | | y=7.25x+75 | | 2x+1=43 | | 2x+2+2X=28 | | log[5]x+log[5](x-24)=2 | | 214-5x=31x+18 | | x^2=-3x+1 | | 3x+8=70-10x | | 4v^2-10=-73 | | x^2+45=-12x | | 2x^2-108=0 | | 2x^2-6=-16 | | 2n^2-6=-16 | | 5x+56=-5 | | D=4+9-11 | | 6.6666666T=18 | | 2d^2=12d-16 | | 16t^5+4t= |

Equations solver categories